Awareness of the Effects of Climate Change and Use of Amelioration Techniques Among Rural Farmers in Akinyele Local Government, Oyo State - Osikabor, Benson; Ogunleye, Dolapo Olumide; David, Esther Olufunmilayo (Journal of Sustainability and Environmental Management, 2025)
This study investigated farmers’ awareness of the effect of climate change and the use of amelioration techniques in Akinyele Local Government, Oyo State. A multistage sampling technique was employed to survey 150 farmers using a well-structured questionnaire; only 117 were retrieved. The data collected were analysed using descriptive statistical tools, while the chi-square was used to test the hypothesis. According to the analysis, 44.4% of respondents were in the 31-40 age bracket, 53.8% had access to early childhood education, and 97.4% were aware of the impact of climate change on productivity. The respondents obtained information from the media (63.2%), extension worker visits, and government officials. The chi-square analysis revealed a significant relationship between respondents’ socioeconomic characteristics and their awareness of climate change. Results showed that the amelioration technique used to adapt to climate change was affected by Gender (x2=56.077, p< 0.005), Age (x2-59.581, p<0.005), Religion (x2=9.308, p<0.005), Marital status (x2=61.077, p <0.005), and educational level (x2-36.974, p<0.005). The recommendations were that effective adaptation measures should be subsidised and accessible to all farmers experiencing problems. There is also a need to organise more targeted programs and sensitisation on climate change to strengthen climate change adaptation, especially in rural areas.